Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
ANSWER X=4. You basically plug what y equals to into the second equation the solve for x.
Answer:
x = 4
y = -7 or (-7, 4)
Step-by-step explanation:
y = -2x + 1
4x + y = 9 replace y in the second equation with (-2x + 1) since y is equal to it
4x + (-2x + 1) = 9 add like terms
2x + 1 = 9 subtract 1 from both sides
2x = 8 divide both sides by 2
x = 4 since y = -2x + 1 replace x with the value we found
y = (-2) × 4 + 1 = -7
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.